2004
DOI: 10.1002/micr.10190
|View full text |Cite
|
Sign up to set email alerts
|

VEGF‐promoted surgical angiogenesis in necrotic bone

Abstract: The ability of vascular endothelial growth factor (VEGF) to accelerate neoangiogenesis from implanted arterovenous (AV) bundles in necrotic bone was evaluated. A saphenous AV bundle was placed in a necrotic segment of rabbit ilium. In group II, VEGF (100 ng/h x 3 days) was administered by continuous infusion. Bone blood flow was measured with radioactive-labeled microspheres, and capillary density was determined by microangiography combined with Spälteholtz bone clearing at 1, 2, and 4 weeks. Neovascularizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Previous studies have shown that VEGF gene transfer or direct administration of VEGF can promote surgical angiogenesis in necrotic bone (36)(37)(38); these studies, however, did not provide evidence regarding bone tissue regeneration or reparative osteogenesis. In a rat femoral head model of vessel deprivation-induced osteonecrosis, high VEGF expression accounted for the striking bone resorption-related remodeling of necrotic debris early during repair, with subsequent substitution by newly formed bone (39,40).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that VEGF gene transfer or direct administration of VEGF can promote surgical angiogenesis in necrotic bone (36)(37)(38); these studies, however, did not provide evidence regarding bone tissue regeneration or reparative osteogenesis. In a rat femoral head model of vessel deprivation-induced osteonecrosis, high VEGF expression accounted for the striking bone resorption-related remodeling of necrotic debris early during repair, with subsequent substitution by newly formed bone (39,40).…”
Section: Discussionmentioning
confidence: 97%
“…VEGF acts in a paracrine and autocrine manner on endothelial cells as a heparin-binding homodimeric glycoprotein (1). VEGF gene transduction has also been found to promote bone marrow cell and endothelial cell proliferation, and induce lumen formation in vitro (2,3). Therefore, the VEGF gene is considered a plausible biological candidate for ONFH.…”
Section: Introductionmentioning
confidence: 99%
“…The alternative is to detect GFP immunochemically using antibody to GFP. Direct VEGF administration can improve blood flow and neovascularization in necrotic bone [38]. In addition to its effects on angiogenesis, VEGF plays an important role in bone growth and repair by interacting with other growth factors [35,36].…”
Section: Limitationsmentioning
confidence: 99%